Proposal for Development of a Graphite Plant - Kazmi, K. R.; Anwar, M. Shafique; Bhatt, M. Arif i; Shah, W. A. (Biological Sciences - PJSIR, 2007)
The design of a commercial graphite processi ng plant is descri bed on the basis of results of beneficiation of a graphite deposit origi nati ng from the Malakand area of North Western Frontier Provi nce (NWFP) of Pakistan. The test work was carried out on the bench scale followed by trials on the pi lot plant to define all process parameters necessary for the production of graphite concentrate. The Malakand ore contai n i ng about I 0-1 6% graphitic carbon was upgraded by froth flotation techniq ue. It is important to note that regrindi ng of the rougher concentrate followed by three cleani ngs of rougher concentrate and reci rcu lati ng the cleaner tailings to the rougher flotation circuit ensured a final concentrate grade of 83-85%, @ > 70% recovery. The pilot scal e flotation tests were carried out @ 75-100 kg of ore per h and 7.5-10.0 kg graphite concentrate were produced per batch. Based on these tests, a commercial plant to handle 50 tons of ore per day (8 h sh ift) has been proposed. The proposed plant costing Rs.26.89 million will daily produce about 5 tons of graphi te concentrate. Graphite concentrate , produced @ Rs. I 0.95 per kg on the proposed processi ng plant, will be considerably cheaper.